Prognostic Value of Blood Urea Nitrogen to Albumin Ratio in Elderly Critically Ill Patients with Acute Kidney Injury: A Retrospective Study - Sinem Bayrakçı; Elif Eygi (Medicina)
Background and Objectives: Acute kidney injury (AKI) is common in intensive-care unit (ICU) patients and is associated with increased mortality. Elderly patients tend to have more comorbid chronic diseases and are more prone to AKI than younger populations, resulting in higher rates of hospitalization and a higher incidence of AKI. Our aim in this study was to investigate the prognostic utility of BUN/albumin ratio (BAR) in predicting mortality in elderly critically ill patients with AKI. Materials and Methods: This study was conducted retrospectively on 154 elderly patients with AKI who were admitted to the ICU between October 2023 and September 2024.Data on the following demographic, clinical, and laboratory parameters were retrospectively collected from medical cards and electronic records. Results: In the non-survivor group, among comorbidities, lung disease was higher (p < 0.05), GCS was lower, and APACHE II was higher among clinical scores (p < 0.001). In the non-survivor group, diuretic use (p = 0.03), oliguria, RRT, vasopressor requirement, sepsis, and MV rates (p < 0.001),as well as BUN, phosphate, LDH, Crp, APTT, INR, and BAR rates, were higher (all p < 0.05) and albumin was lower (p = 0.01). Cut-off values of BUN, albumin, and BAR variables according to mortality status were determined by an ROC curve analysis, as follows:48.4 for BUN (p = 0.013), 31.5 for albumin (p = 0.001), and 1.507 for BAR (p = 0.001).According to the results of the ROC analysis performed to predict in-hospital mortality, the BAR level reached an AUC value of 0.655. A BAR value above 1.507 increases mortality by 3.944 times (p = 0.023). Conclusions: BAR is a simple and accessible biomarker that may serve as a predictor of in-hospital mortality in elderly patients with AKI. Its use may aid early risk stratification and decisionmaking in the ICU.